2008
DOI: 10.1016/j.cellbi.2008.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Induction of G1 phase arrest and apoptosis in MDA‐MB‐231 breast cancer cells by troglitazone, a synthetic peroxisome proliferator‐activated receptor γ (PPARγ) ligand

Abstract: Peroxisome proliferator-activated receptor gamma (PPARgamma) ligands inhibit cell proliferation and induce apoptosis in cancer cells. Here we wished to determine whether the PPARgamma ligand induces apoptosis and cell cycle arrest of the MDA-MB-231 cell, an estrogen receptor alpha negative breast cancer cell line. The treatment of MDA-MB-231 cell with PPARgamma ligands was shown to induce inhibition of cell growth in a dose-dependent manner as determined by MTT assay. Cell cycle analysis showed a G1 arrest in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 22 publications
1
34
0
Order By: Relevance
“…Second, DMC was effective in modulating the expressions of various PPAR γ -targeted gene products associated with cell cycle progression and apoptosis in MCF-7 cells, including cyclin D1, CDK6 [17], Bcl-2, XIAP [18], and COX-2 [19] (Figure 3(d)). In addition, the drug effect on the expression of NF- κ B/p65 was interrogated in light of a recent report that PPAR γ acts as an E-3 ligase targeting p65 degradation [27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, DMC was effective in modulating the expressions of various PPAR γ -targeted gene products associated with cell cycle progression and apoptosis in MCF-7 cells, including cyclin D1, CDK6 [17], Bcl-2, XIAP [18], and COX-2 [19] (Figure 3(d)). In addition, the drug effect on the expression of NF- κ B/p65 was interrogated in light of a recent report that PPAR γ acts as an E-3 ligase targeting p65 degradation [27].…”
Section: Resultsmentioning
confidence: 99%
“…Many of these PPAR γ agonists exhibit antiproliferative activities against many types of cancer cells including those of colon, prostate, and breast, suggesting the potential use of these agents in cancer therapy or prevention [16]. Evidence suggests that PPAR γ activation leads to the transcriptional suppression of a series of signaling effectors associated with tumorigenesis, including cell cycle regulators (cyclin D1, cyclin E, and cyclin-dependent kinase (CDK) 6) [17], antiapoptotic proteins (Bcl-2 and XIAP) [18], and cyclooxygenase- (COX-) 2 [19], thereby facilitating apoptotic death in cancer cells [20, 21]. Therefore, PPAR γ is recognized as a therapeutically relevant target for cancer therapy [22, 23].…”
Section: Introductionmentioning
confidence: 99%
“…A subsequent study demonstrated that decreased viability and enhanced apoptosis in MCF-7 cells treated with 15-PG-J2 were accompanied by an impairment of mitochondrial function and increased ROS production (Pignatelli et al, 2001). The induction of cell death by synthetic ligands such as troglitazone and rosiglitazone was only seen when cells were treated with either over-saturation doses (Yu et al, 2008, Mody et al, 2007)or in combination with other agents (Mody et al, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…They exhibit potential antitumor effects on numerous types of cancers (4)(5)(6)(7)(8)(9)(10), including prostate cancer (11)(12)(13). A previous study performed on prostate cancer cell lines has demonstrated that troglitazone (TGZ) decreases cellular proliferation, which is associated with increased expression levels of glutathione peroxidase 3 (GPx3) (11).…”
Section: Introductionmentioning
confidence: 99%